Septic implantation syndrome in dogs and cats: a distinct pattern of endophthalmitis with lenticular abscess. (19th July 2012) - Bell, Cynthia M.; Pot, Simon A.; Dubielzig, Richard R.
Abstract Objective To summarize the clinical and pathologic findings in a group of dogs and cats with progressive clinical ocular disease, which were diagnosed with suppurative endophthalmitis and lens capsule rupture. Animals studied Twenty cats and forty‐six dogs that underwent unilateral enucleation or evisceration for intractable uveitis and/or glaucoma. Procedure Biopsy submission requests and microscopic case material were evaluated for clinical and histological features, including history of ocular trauma, duration of ocular disease, pattern of inflammation, and the presence of intralenticular microorganisms. Results The median duration for cats and dogs was 6 and 5 weeks, respectively. A history of trauma was reported for four (20%) cats and 18 (39%) dogs. All confirmed cases of trauma—three in cats and 14 in dogs—were caused by a cat scratch. Microscopically, all cases had suppurative endophthalmitis centered on the lens, lens capsule rupture, cataract, and lenticular abscess. Infectious organisms were identified by Gram stain within the lens of 14 (70%) cats and 30 (65%) dogs. Gram‐positive cocci were seen most commonly. Male cats were overrepresented as compared to females. There were no apparent gender, age or breed predilections in dogs. Conclusions A unique pattern of slowly progressive or delayed‐onset endophthalmitis with lens capsule rupture, lenticular abscess, and frequently intralenticular microorganisms is associated with traumatic penetration of the globe and lens capsule. The term Septic Implantation Syndrome (SIS) is favored in lieu of 'phacoclastic uveitis' to avoid confusion with phacolytic uveitis and to clearly implicate the role of intralenticular microorganisms in the pathogenesis.